How to kill your family ebook A novel. - Mackie, Bella (2022)
Outrageously funny, compulsively readable, and subversive, How to Kill Your Family is a wickedly dark romp about class, family, love . . . and murder. Coming soon as an 8-episode series on Netflix, executive produced and starring Anya Taylor-Joy. Bella Mackie's debut novel is driven by a captivating first-person narrator who talks of self-care and social media while calmly walking the reader through her increasingly baroque acts of murder. But then, Grace is imprisoned for a murder she didn't commit.... When Grace Bernard discovers her absentee millionaire father has rejected her dying mother's pleas for help, she vows revenge and coldly sets out to get her retribution—by killing them all, one by one. This darkly humorous debut novel follows a cunning antihero as she gets her revenge. "Funny, sharp, dark, and twisted." —Jojo Moyes When I think about what I actually did, I feel somewhat sad that nobody will ever know about the complex operation that I undertook. Getting away with it is highly preferable, of course, but perhaps when I'm long gone, someone will open an old safe and find this confession. The public would reel. After all, almost nobody else in the world can possibly understand how someone, by the tender age of twenty-eight, can have calmly killed six members of her family. And then happily got on with the rest of her life, never to regret a thing.